Rancang Bangun e-Recruitment untuk Sekolah Kejuruan dengan Model Knowledge Centered Services (KCS) - Edi Ismanto; Eka Pandu Cynthia (Faculty of Teacher Training and Education, 2019)
Abstrak Sekolah menegah kejuruan (SMK) merupakan sekolah yang menyiapkan peserta didiknya agar trampil dan siap untuk bekerja,salah satu indikator keberhasilan dari sekolah kejuruan bahwa peserta didiknya harus banyak diserap atau dipakai dalam dunia industry ataupun perusahaan, untuk mencapai tujuan tersebut sekolah kejuruan harus membangun relasi dengan dunia industry ataupun perusahaan agar memudahkan lulusan dari peserta didiknya dalam mencari pekerjaan sesuai kompetensinya.Dengan pengembangan model e-recruitment ini merupakan salah satu upaya untuk mempermudah hubungan antara sekolah,perusahaan, dan lulusan peserta didiknya, dalam mendapatkan dan menyampaikan informasi lowongan pekerjaan yang dibutuhkan.Model e-recruitment ini dikembangkan dengan pendekatan Knowledge Centered Services (KCS) yang menekankan pengetahuan sebagai asset terpenting dengan sistemdua loop kontinyu, Loop Solve dan Loop Evolve sehingga meningkatkan sistem kerja dari pelayanan e-recruitment. Kata kunci:e-recruitment,knowledge centered services (KCS), Abstract Vocational high school (SMK) is a school that prepares students to be skilled and ready to work, one indicator of the success of vocational schools is that students must be absorbed or used in the world of industry or companies, to achieve this goal vocational schools must build relationships with the world of industry or companies to make it easier for graduates of their students to find work according to their competencies. By developing this e-recruitment model, it is one effort to facilitate the relationship between schools, companies, and graduates of students, in obtaining and delivering the required job information. This e-recruitment model was developed with the Knowledge Centered Services (KCS) approach which emphasizes knowledge as the most important asset with a continuous two-loop system, Loop Solve and Loop Evolve so as to improve the work system of e-recruitment services. Keywords:e-recruitment, knowledge centered services (KCS),